Analytical and functional evaluation of financial parameters of strategic innovation cycles in construction companies based on the concepts of method of Cost allocation by activities - Ryzhakova, G.; Bilous, B.; Tsai, M.; Rizun, D. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the analysis of methods for assessing the financial parameters of strategic innovation cycles in construction companies, in particular using the concept of "Method of cost allocation by activities". In the conditions of constant changes in the construction market, in particular the introduction of innovations, it is important to ensure effective assessment of financial indicators, which contributes to increasing the stability and competitiveness of the company. The method of cost allocation based on activities is one of the most effective tools for calculating costs and determining the feasibility of investments in strategic innovations. The article considers theoretical aspects and practical aspects of applying this method to assess innovation strategies in construction companies. The main task is to determine the effectiveness of innovation cycles from the point of view of their impact on the financial parameters of the company. The analysis is carried out through cost allocation, where each activity is assessed based on its impact on the company’s overall costs. This approach allows not only to calculate costs, but also to identify areas for optimizing resources and reducing costs. It is important to note that the application of the method allows for a clear understanding of the effectiveness of various strategic initiatives and allows predicting their economic effect in conditions of dynamic changes in the market. The key aspects of the article are the analysis of the use of the concept in construction companies, the advantages of using the method to improve the strategic management process, as well as opportunities for further development and implementation of innovations in conditions of growing competition. The implementation of this method allows construction companies to manage resources more effectively, reduce costs and increase competitiveness. In particular, it is important that the method contributes to better allocation of investments, risk assessment and increased level of management in the processes of implementing innovations. In addition, this method allows for optimizing costs at different stages of project implementation, thereby improving the overall efficiency of construction companies. Thus, the application of this concept not only improves financial results, but also strengthens the company’s position in the competitive market.